RELATIONSHIP BETWEEN HIGHER-ORDER THINKING SKILLS (HOTS) AND ENGLISH ACHIEVEMENT - Ernis Sholikah; Suprihadi Suprihadi; Nuraeningsih Nuraeningsih (Universitas Muria Kudus, 2021)
Higher-order thinking skills (HOTS) is a new concept of thinking in Curriculum 2013 in Indonesia, which is based on the revised top three levels in Bloom’s Taxonomy: analyzing, evaluating, and creating. This survey research used 44 students who were purposively sampled. The objective of this research was to determine if there was a linear correlation between HOTS and the English achievement of the eleventh grade students of SMA N 2 Kudus. Using Pearson’s Product Moment Correlation in the level of significance .05 and degree of freedom 42, this research showed that there was a high positive significant linear correlation between HOTS and the English achievement of the eleventh grade students of SMA N 2 Kudus. Key words: HOTS, taxonomy, curriculum 2013, English achievement